PENERAPAN PEMBANGKIT TENAGA SURYA PADA OBJEK WISATA KAMPUNG SAWAH GUNA MENGURANGI BIAYA PEMBELIAN ENERGI LISTRIK - Rimbawati, Rimbawati; Siregar, Zulkifli; Yusri, Mohammad; Al Qamari, Muhammad (Universitas Muhammadiyah Tapanuli Selatan, 2021)
This community service program aims to implement a Solar Power Plant (PLTS) to provide electrical energy in tourist areas called rice field tourism, in order to reduce the cost of purchasing electrical energy for managers. Besides, it is also a means of education for visitors to introduce green energy in the future. The design of PLTS is adjusted to the requirements of the load that will be served at the tourist attraction. Before carrying out development, the Team first conducted outreach to local residents to introduce technology in rural areas. After the rotating program for managing tourism objects, in this case BUMDes Johar Mandiri, was given training in the operation, maintenance / maintenance of the solar power generation system, so that after the program it was able to solve the troubleshooting that occurred both in the generation system, control and distribution system. The resulting capacity of the Solar Power Plant in this Sawah Tour is 3500 WP which is used to meet all lighting needs. With this program, managers can reduce costs by Rp. 3,000,000 / month for electricity needs.